KETIDAKSEIMBANGAN SISTEM SOSIAL PENYEBAB BENCANA ALAM - Chairil Siregar (Jurnal Sosioteknologi, 2007)
Human beings have culture and with this, they can do any activities. However, the enculturization has deviated; man cannot adapt with the culture system on the social environment. This behavior has caused the nature phenomena evolve from the God's destiny. As a civilized creature, man has done improper things, so it resulted in the culture imbalance. The material culture has moved much further than the nonmaterial culture; consequently, the natural disaster turn up.